Influence of the Police Force on Black Lives Matter - Gio Hong, (Technium Social Sciences Journal, 2020)
With the recent revival of the Black Lives Matter movement reaching all corners of the world, I wanted to dive deeper into the topic and figure out what the stem issues were. More precisely, I set my eyes on unearthing what kind of correlation the police force had with the movement. What made the movement change so much this year compared to the Black Lives Matter movement in 2014? Did the cops have any influence on this change? Through my thorough research, I concluded that the decisions made by the police force has influenced both the aim of the Black Lives Matter movement and the purpose as a whole. Due to the conflicts between the police and protesters all over the world, the aim of the Black Lives Matter movement has shifted to future police implications; for the first time in movement history, advocates fought for the defunding of police. Instead of solely focusing on systematic racism and police brutality, protesters spread awareness for topics like defunding the police and removing the usage of loaded firearms. Compared to 2014’s movement, which focused on systematic racism and injustice, this year’s movement saw a great uprising of police animosity.